Quantitative and qualitative analyses of grafted okra for corrosion inhibition of mild steel in acidic medium - Sulaimon, Aliyu Adebayo; Murungi, Pearl Isabellah; Tackie-Otoo, Bennet Nii; Nwankwo, Princess Christiana; Bustam, Mohamad Azmi (Frontiers in Chemistry, 2023)
Natural plant polymers demonstrate effective corrosion inhibition abilities, because of their numerous binding sites and excellent adsorption abilities. In this study, the Box-Behnken method, gravimetric and electrochemical analyses were used to design and investigate the corrosion inhibition potential of a modified graft polymer of okra for mild steel in a 1M HCl medium. The influence of inhibitor concentration, temperature, and time were also investigated. Qualitatively, the Fourier Transform Infrared (FTIR) spectroscopy, Thermogravimetric Analysis (TGA), and Field emission scanning electron microscopy (FESEM) were used to characterize the extracts and evaluate the metal’s surface morphology. The quantitative analyses showed that the inhibition efficiency (IE) of the modified natural polymer extract increased with concentration and reached 73.5% at 800 ppm, with a mixed-type mode of inhibition. From the response surface methodology, it was revealed that temperature influences the IE more than concentration and immersion time. The optimized IE using the desirability function showed the possibility of attaining 88.2% inhibition with inhibitor concentration at 142.3ppm, temperature at 60.4°C, and an immersion time of 22.4h. The new functional groups in the hybrid polymer revealed by FTIR analysis shows that grafting improved the inhibitor’s adsorption abilities. TGA analysis confirmed the high thermal stability of the extract which highlights the inhibitor’s strong adsorption and efficiency for high temperatures. FESEM analysis indicated evidence of inhibitor adsorption onto the metal surface. These findings suggest that the grafting of okra with acrylamide enhances its inhibition properties and contributes to its functionality as a cost-effective plant-based alternative inhibitor against corrosion for mild steel facilities.